Health behavior of Austrian tertiary students focusing on diet type linked to sports and exercise—first glimpse of results from the “sustainably healthy—from science 2 high school and university” study - Wirnitzer, Katharina C.; Motevalli, Mohamad; Cocca, Armando; Tanous, Derrick R.; Wirnitzer, Gerold; Wagner, Karl-Heinz; Schätzer, Manuel; Drenowatz, Clemens; Ruedl, Gerhard; Kirschner, Werner (Frontiers in Public Health, 2023)
Background There is a strong association between lifestyle behavior and health status. While young adulthood is a critical period for adopting and stabilizing lifelong healthy behavior, university life is independently associated with psychological stressors that may further affect health and well-being. Objective The present multidisciplinary study aimed to examine the health behavior of Austrian college and university students, differentiated based on diet types (vegan, vegetarian, and omnivorous) and physical activity (PA) habits. Methods Following a cross-sectional study design, a total number of 6,148 students (65.3% females; 66.1% bachelor students, 67.0% from urban areas; mean age: 24.8 years) from 52 Austrian college/universities participated in an online survey and provided data on sociodemographic characteristics, dietary patterns, PA habits, and other lifestyle behavior characteristics, including alcohol intake and smoking. Results Across the total sample, 74.0% had a normal weight (BMI = 18.5–25.0 kg/m2), while the prevalence of overweight/obesity (BMI ≥ 30.0 kg/m2) was lower in females than males and more in rural than urban students (p < 0.01). The general prevalence of vegetarian and vegan diets was 22.8 and 6.0%, respectively, with a predominance of females, graduates, and urban students compared to their peers (p < 0.01). The majority of students (79.3%) had a regular engagement in sport/exercise, with a predominance of vegetarian or vegan students compared to omnivores (p < 0.01). Vegans and vegetarians had a lower alcohol intake (p < 0.01) but no differences in smoking habits (p > 0.05) compared to omnivores. Students engaging in sport/exercise had a lower smoking rate and higher intake of fruits, vegetables, and fluids compared to inactive students (p < 0.01). Conclusion The present findings suggest that diet type and PA habits of college/university students have an impact on other health behaviors, highlighting the interconnected nature of lifestyle habits and health behavior.